PASTORAL KONSELING KEPADA NARAPIDANA KRISTEN DI LEMBAGA PEMASYARAKATAN CIPINANG - Buce D Patty; Rikardo P Sianipar (STT Bethel The Way, 2019)
This mini thesis research discusses about the implementation of effective counseling service inCipinang. Penitentiary that need guidance and guidance of servant og God. Seeing from the manycrimes in Cipinang Prison involving Chistian Prisoners. His hoped that through effective pastoralcounseling can serve them toward a genuine conversion.This research is done by using qualitative descriptive method, which is conducting interview,observation, and analysis to Christian prisoner of narcotics case, gambling, corruption, and sexualharassment. Their response to counselling is so strong that they are in dire need of regularcounselling services.The author concludes that effective pastoral counseling services to Christian Prisoners need to beintensified. Similarly the pattern of guidance of prisoners of correctional Prison by Cipinang Prisonofficers needs to be developed intensively. Through these two methods can impact on moreeffective coaching results, can awaken Christ’s congregation in Cipinang Penitentiary, prepared tobe a servant of God.